Policies within the EU multi-level system: instruments and strategies of European governance - Heinelt, Hubert; Knodt, Michèle (Nomos, 2011)
"This book gives an overview over the central governance policies of the EU. Each chapter focuses on the development of an individual policy, therefore the essential instruments of each policy are considered, as well as the main actors which play an important role in agenda-setting, policy formulation, and implementation. In addition, the meaning of multi-level governance is analyzed for each policy."--Publisher's description
Enth. 19 Beitr. - Literaturangaben
Keywords: European Union -- History; Europäische Union; European Union countries -- Politics and government; Aufsatzsammlung; Governance; Mehrebenen-Verflechtung